Advances in identification and selection of personalized neoantigen/T-cell pairs for autologous adoptive T cell therapies. (1st January 2021) - Kast, Florian; Klein, Christian; Umaña, Pablo; Gros, Alena; Gasser, Stephan
ABSTRACT: Based on the success of tumor-infiltrating lymphocytes (TIL)-based therapies, personalized adoptive cell therapies (ACT) targeting neoantigens have the potential to become a disruptive technology and lead to highly effective treatments for cancer patients for whom no other options exist. ACT of TIL, peripheral blood or gene-engineered peripheral blood lymphocytes (PBLs) targeting neoantigens is a highly personalized intervention that requires three discrete steps: i) Identification of suitable personal targets (neoantigens), ii) selection of T cells or their T cell receptors (TCRs) that are specific for the identified neoantigens and iii) expansion of the selected T cell population or generation of sufficient number of TCR modified T cells. In this review, we provide an introduction into challenges and approaches to identify neoantigens and to select the Adoptive Cell Therapy, ACT, Neoantigen, T cell, Cancer respective neoantigen-reactive T cells for use in ACT.